Agricultural and Food Systems Transformation for Better Food Security and Nutrition in Eurasia - Akramov, Kamiljon T. (2018)
Kamiljon Akramov POLICY SEMINAR Agricultural and Food Systems Transformation for Better Food Security and Nutrition in Eurasia Co-Organized by IFPRI, the World Bank, and CGIAR Research Program on Policies, Institutions, and Markets (PIM) NOV 13, 2018 - 01:20 PM TO 02:20 PM EST